AN ANALYSIS ON THE TRANSLATION SRATEGIES AND THE QUALITY ASSESMENT OF SOME HUMOROUS EXPRESSION - Alief Sutantohadi (Universitas Katolik Widya Mandala Surabaya, 2017)
This descriptive qualitative research is conducted to describe thestrategies are used by the writer to translate the joke in the book â€œLetâ€™sJoke and Enrich Your Vocabularyâ€ and also to know the quality of thetranslation assesed from Accuracy and Acceptability. This researchapplies purposive sampling since the samples are chosen anddetermined based on criteria. The result of this research showed therewere 9 translation strategies, named Shift (91 data or 72.8 %), Literaltranslation (9 data or 7.2 %), Addition (7 data or 5.6 %), Deletion (6data or 4.8%), Borrowing (5 data or 4.0%), Free translation (3 data or2.4 %), Cultural substitution (2 data or 1.6 %), Naturalization (1 datumor 0.8 %), Synonym (1 datum or 0.8 %). The accuracy assesmentshowed there were 73 data (81.1 %) considered to be accurate, 14 data(15.6 %) considered to be less accurate, 3 data (3.3 %) considered to beinaccurate. The strategies resulting from the accurate translation aredeletion, literal, borrowing, naturalization, synonym and culturaltranslation. The strategies resulting from the less accurate andinaccurate translations are addition, shift and free translation. From theacceptability assesment, there are 66 data (73,33 %) considered to beacceptable translation, 15 data (16, 67 %) considered to be lessacceptable translation, 9 data (10 %) considered as unacceptabletranslation. The strategy resulting from the high level of acceptabletranslation is addition. The strategy resulting from the unacceptabletranslation was the use of synonym.